Positive Affect as a Buffer Between Chronic Stress and Symptom Severity of Emotional Disorders. (September 2019) - Sewart, Amy R.; Zbozinek, Tomislav D.; Hammen, Constance; Zinbarg, Richard E.; Mineka, Susan; Craske, Michelle G.
Research has demonstrated that stressors play a critical role in the development of generalized anxiety disorder (GAD), social anxiety disorder (SAD), and major depressive disorder (MDD). Separately, deficits in positive affect (PA) have been identified in GAD, SAD, and MDD. Whereas previous research has linked the buffering effects of PA in chronic illness, such effects have yet to be investigated for chronic stressors and emotional disorder–related symptom severity. The purpose of the present study was to examine PA as a moderator of chronic interpersonal and noninterpersonal stress on GAD, SAD, and MDD symptom severity. Using a multilevel statistical approach with a sample of adolescents and young adults ( N = 463), PA was found to moderate significantly the relationship between chronic interpersonal stress and symptom severity for MDD and SAD. Findings suggest that in times of chronic interpersonal stress, higher PA may serve as a buffer from development of SAD and MDD symptoms.